(untitled) (Medico Legal Update, 2020)
Massage is the oldest touch therapy known to man. With massage is expected to improve the evaporation process by widening blood vessels and opening pores in the child’s body so that fever is expected to quickly go down. This study aims to identify whether there is an effect of massage therapy on the body temperature of children who have a fever. This research used pre and posttest control group design. Research location in Hospital Dr.Soekardjo Tasikmalaya. The sample size were 41 people. The result was a significant difference in the average body temperature before and after the compress (p-value=0.000) and massage therapy (p-value=0.000) in both the first and second measurements. Comparison of temperature reduction before and after the compress and massage therapy results were significant at first measurement (p-value=0.002) but not significant in the second measurement (p-value=0.0388). It is expected that nurses on duty in the children’s room can increase the participation of families in handling health in children, especially children with fever. And for researchers, further research should be done regarding massage therapy with the use of topical alternative medicine to further enrich family knowledge in the management of sick children.